PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD TERHADAP MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN MATEMATIKA: PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN FLASHCARD TERHADAP MINAT BELAJAR SISWA PADA MATA PEMBELAJARAN MATEMATIKA - Dinda Citra Larasat; Waskito Aji; Muhammad (STKIP Subang, 2025)
Based on observations by researchers at Krandon Lor 01 Public Elementary School, particularly in second grade, many students' learning outcomes are below average. This raises the issue of a lack of enthusiasm for mathematics. Therefore, based on this background, researchers will examine the effect of flashcard learning media on the learning interest of second-grade students at Krandon Lor 01 Public Elementary School, specifically in mathematics, on addition and subtraction. The purpose of this study was to determine the effect of flashcard learning media on the learning interest of students at Krandon Lor 01 Public Elementary School, particularly second-grade students. The research method used was quantitative with a purposive sampling technique. The results showed that flashcard learning media significantly influenced student learning interest, with a negative correlation. Therefore, an evaluation of the types and methods of using learning media is needed to make it more engaging, relevant, and able to increase student learning interest. Future researchers are advised to further examine the influence of flashcard media with a larger sample size, at different levels, or by adding other variables such as learning motivation and learning outcomes, to further understand the role of flashcards in learning.